2017
DOI: 10.1175/jpo-d-16-0160.1
|View full text |Cite
|
Sign up to set email alerts
|

ACC Meanders, Energy Transfer, and Mixed Barotropic–Baroclinic Instability

Abstract: Along-stream variations in the dynamics of the Antarctic Circumpolar Current (ACC) impact heat and tracer transport, regulate interbasin exchange, and influence closure of the overturning circulation. Topography is primarily responsible for generating deviations from zonal-mean properties, mainly through standing meanders associated with regions of high eddy kinetic energy. Here, an idealized channel model is used to explore the spatial distribution of energy exchange and its relationship to eddy geometry, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 48 publications
7
61
0
Order By: Relevance
“…This is also in agreement with the linear predictions which say that any zonal variation in bottom topography enhances the baroclinic instability [Chen and Kamenkovich, 2013;Hart, 1975]. In a study of the North Atlantic jets, Kamenkovich et al [2009] also found both kinds of eddy feedbacks [also see Barthel et al, 2017;Melnichenko et al, 2010;Youngs et al, 2017]. It is important to note that if eddy field is computed by high-pass time filtering in a stationary frame of reference, then the resulting eddy field would also include the drifting jets.…”
Section: Nonlinear Effects and The Role Of Eddiessupporting
confidence: 84%
See 1 more Smart Citation
“…This is also in agreement with the linear predictions which say that any zonal variation in bottom topography enhances the baroclinic instability [Chen and Kamenkovich, 2013;Hart, 1975]. In a study of the North Atlantic jets, Kamenkovich et al [2009] also found both kinds of eddy feedbacks [also see Barthel et al, 2017;Melnichenko et al, 2010;Youngs et al, 2017]. It is important to note that if eddy field is computed by high-pass time filtering in a stationary frame of reference, then the resulting eddy field would also include the drifting jets.…”
Section: Nonlinear Effects and The Role Of Eddiessupporting
confidence: 84%
“…For example, eddies play a major role in the dynamics of the Antarctic Circumpolar Current (ACC) [Abernathey and Cessi, 2014;Thompson and Naveira Garabato, 2014]. Recent studies have shown that the behaviour of the Reynolds stress term and form stress term can change abruptly around the topographic features in the Southern Ocean, where in different parts of the ocean eddies are seen to be forcing the large-scale flow as well as gaining energy via a barotropic energy source [Barthel et al, 2017;Youngs et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…Friction alone is able to produce asymmetric flows over symmetric ridges, and therefore topographic form stress, even without transients. However, from the line of reasoning above, we infer that transient eddies (generated either by baroclinic instability or barotropic processes) act to sharpen and barotropize flow over bathymetry, leading to an even more asymmetric flow over ridges (Youngs et al, 2017), which can enhance the net momentum sink due to topographic form stress. Therefore, as an alternative to the common view that baroclinic instability is an integral component of eddy saturation, we propose that eddy saturation occurs as a consequence of feedbacks between transient eddies and the mean flow which creates topographic form stress and, in turn, balances the momentum input from wind stress (Figures 4c and 4d).…”
Section: Discussionmentioning
confidence: 88%
“…In addition to the evidence for strong bottom flows, some recent work has emphasized the importance of the bathymetry in setting up standing meanders in the course of the ACC and in producing strong interaction between barotropic and baroclinic fluid motions (Barthel et al, 2017;Youngs et al, 2017). Furthermore, these meanders play a crucial role in balancing the momentum through topographic form stress and thus determining the ACC transport (Katsumata, 2017;Thompson & Naveira Garabato, 2014).…”
Section: 1029/2019gl084117mentioning
confidence: 99%
“…Processes involving the barotropic circulation and its interaction with the bathymetry may also participate in reducing the sensitivity of the ACC's baroclinicity. The analysis of the energetics of an ACC standing meander in Youngs et al (2017) reveals that barotropic instability plays a leading role in the energy budget of the meander and suggests that baroclinic conversion alone is insufficient to describe both the stratification and distribution of EKE. The standing meanders that form through the interaction of the barotropic flow with the topography contribute to the bottom form stress and may also participate in the saturation process (Thompson and Naveira Garabato, 2014;Katsumata, 2017).…”
Section: Implications For the Eddy Saturation Processmentioning
confidence: 99%